Integrated Care for Comprehensive Management of Patients with Osteoarthritis: Program Development and Implementation - Rucinski, Kylee; Crecelius, Cory R.; Stucky, Renée; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2023)
Treatment of symptomatic osteoarthritis (OA) is often complicated by comorbidities, which put patients at potentially higher risks following operative interventions. Management of these comorbidities is usually separate from orthopaedic care, with patients invited to return to their orthopaedic surgeon once surgical risk factors are better controlled. However, this practice can lead to disjointed care, resulting in uncertainty, mistrust, unmanaged pain, and dissatisfaction for patients. Integrated care teams provide an effective option for coordinated comprehensive nonoperative and preoperative management of patients with knee OA and medical comorbidities. The objective of this article is to summarize the process for implementation of an integrated program to manage patients with symptomatic knee OA and the initial outcomes at our institution as an example of the effects of integrated patient management in orthopaedics. At the author's institution, an integrated program was implemented, successfully addressing the unmet need for coordinated care for patients with bone and joint health problems and medical comorbidities. Patients who completed the full program experienced significant improvements in both pain and function. Potential applications for knee surgeons considering implementing integrated care models could include pre- and postoperative management programs, nonoperative management program, and programs seeking to meet key metrics such as improved readmission rates, patient satisfaction, or value-based care. For effective program implementation, careful planning with convenient referral mechanisms, leadership buy-in, and patient-centered communication protocols are required.
Keywords: osteoarthritis; integrated care; knee; pain; exercise; therapy